A sub-200 nanometer wide 3D stacking thin-film temperature sensor. Issue 46 (22nd April 2016) - Huo, Xiaoye; Wang, Zhenhai; Fu, Mengqi; Xia, Jiye; Xu, Shengyong
Abstract : We presented a 3D stacking thin-film temperature sensor with a total width down to 140 nm, a temperature resolution of 40–100 mK, and repeatable sensitivities of 9.6 ± 0.7 μV K −1 and 3.6 ± 0.1 μV K −1 for Cr/Pd and Au/Pd sensors with varied junction size. Abstract : We developed a series of thin-film thermocouples (TFTCs) made from Cr, Au, and Pd long stripes with a width of 90–300 nm and a 10 nm insulating HfO2 layer. The sensors have a three-dimensional sandwich structure, therefore reducing the total width down to 138 nm. Their sensitivity (thermopower) values were measured to be 9.6 ± 0.7 μV K −1 for the Cr/HfO2 /Pd sensors and 3.6 ± 0.1 μV K −1 for the Au/HfO2 /Pd sensors. These sensors showed reproducible and reliable measurement performance with a good temperature resolution of 0.04–0.1 K and a small heat capacity of 3.2–3.5 × 10 −14 J per K per micron length, making them promising candidates for applications in electronic devices, microfluidic systems, and single cell or sub-cell detection as built-in sensors.